Pengaruh Pengelolaan Air Terhadap Pertumbuhan dan Hasil Beberapa Varietas Tanaman Padi (Oryza Sativa L.) - Wahid Mustofa; Muharam Muharam; Yayu Sri Rahayu (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to get the right water delivery pattern to the growth and yield of several varieties of rice plants. The research design uses split plots. The main plot is the provision of water with 3 levels; A1 (Intermittent), A2 (Macak-macak), A3 (Inundated) and tenements are varieties with 3 levels; V1 (Inpari 32), V2 (Inpago 10) and V3 (M400) had 9 treatments each repeated three times so that there were 27 trials. The effect of treatment is analyzed variously and if the F test is 5% significant, then continued with the DMRT test (Duncan Multiple Range Test) at the level of 5%. The results of the experiment showed that there was an interaction between water management with several varieties, namely the number of sapleds (34.83 sapves), the age of flowers (75.33 hst), and the treatment that gave the highest results in each observation parameter, namely on the plant height parameters 42 hst (a2v3), sapled jumah (a3v1), flowering age (a2v2), the number of productive malai (a3v1), weight 1000 grains (a3v3) and milled dry grain (a1v3).